Implementasi Nilai Kebhinekaan Global Dalam Profil Pelajar Pancasila Untuk Menghadapi Krisis Identitas Nasional - Raudya Tuzzahra Maghfirani; Siti Romelah (LPPM Politeknik Pratama, 2023)
The purpose of this research is to find out the implementation of pancasila student profiles in junior high schools, especially the value of global diversity in overcoming the national identity crisis that students are currently experiencing. The research subjects were grade 7 junior high school students who applied merdeka curriculum. The research was conducted with descriptive qualitative. Interviews and documentation are techniques used for data collection. While the analysis uses data reduction techniques, data presentation, verification and drawing conclusions. The results of the study show that the implementation of pancasila student profiles in schools is not optimal, especially the value of global diversity. So that the relation to overcoming the national identity crisis experienced by students cannot be carried out properly due to the many obstacles that arise from the students and teachers.